2012
DOI: 10.1080/00140139.2011.642007
|View full text |Cite
|
Sign up to set email alerts
|

Cost efficiency comparison of four video-based techniques for assessing upper arm postures

Abstract: The cost efficiency of four video-based techniques for assessing upper arm postures was compared. Work sampling techniques were in general more cost efficient than continuous observations since they were labour-saving. Whilst a labour cost dominated the comparison, 'hidden costs', bias and measurement strategy also influenced this dominance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 26 publications
(24 reference statements)
0
46
1
Order By: Relevance
“…This is opposite to what has been reported in a study of hairdressers' upper-arm postures, where video observers overestimated inclination angles (21). A lab-based study identified an observation over-estimation in higher exposure ranges for trunk flexion when compared to opto-electric tracking (51); validation studies of neck flexion also showed observations to over-estimate when compared to an inclinometer (52).…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…This is opposite to what has been reported in a study of hairdressers' upper-arm postures, where video observers overestimated inclination angles (21). A lab-based study identified an observation over-estimation in higher exposure ranges for trunk flexion when compared to opto-electric tracking (51); validation studies of neck flexion also showed observations to over-estimate when compared to an inclinometer (52).…”
Section: Discussioncontrasting
confidence: 54%
“…Thus, by definition, the results obtained by inclinometry were taken to be unbiased (B=0), and the bias, B, of the results obtained by observation was calculated as the difference between mean exposures obtained by observation and the corresponding results according to inclinometry. The combined precision and bias performance of each posture assessment method was calculated as the inverse of the RMSE μ (19,21), which is thus, by definition, equal to 1/ for inclinometry in the present case.…”
Section: Precision and Bias Combinedmentioning
confidence: 99%
See 3 more Smart Citations